Effects of Haptic Feedback on Precision Peg Insertion Tasks Under Different Visual and Communication Latency Conditions - Tomonari Tanioka; Hikaru Nagano; Yuichi Tazaki; Yasuyoshi Yokokohji (Robotics)
This study investigated the role of haptic feedback in precision peg insertion tasks conducted via teleoperation under varying visual resolution and communication latency conditions. Experiment 1 examined the combined effects of haptic feedback and the visual resolution, revealing that haptic feedback significantly reduces the maximum normal force and mental workload, while enhancing subjective operability, particularly in low-visual-resolution conditions. Experiment 2 evaluated the impact of communication latency, showing that the maximum normal force, operability, and mental workload are affected by increased latency. Notably, the maximum normal force is sensitive even to minimal latency (100 ms), whereas the mental workload and operability remain acceptable under lower-latency conditions. These findings underscore the importance of multi-metric evaluations, as different aspects of performance respond differently to latency. Overall, the results demonstrate the critical role of haptic feedback in enhancing task performance and the user experience in teleoperated precision tasks, offering valuable insights for the design and development of more effective and user-friendly teleoperation systems.